1982
DOI: 10.1097/00000658-198212001-00016
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the He Ne Laser and Ultrasound Doppler Systems in the Determination of Viability of Ischemic Canine Intestine

Abstract: One of the most challenging intraoperative dilemmas continues to be determination of viability of ischemic bowel. Many techniques and devices are available to help the surgeon, probably the most useful of which is the ultrasound Doppler. A more recently developed system, the laser Doppler, has a flexible optical fiber and fine tip probe that can be approximated onto or endoscopically passed into the gastrointestinal tract. This study was undertaken to experimentally compare the He Ne laser and ultrasound Doppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

1985
1985
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 3 publications
0
11
0
4
Order By: Relevance
“…Accordingly, LDF has proven useful for measurement of blood flow changes in the cerebral cortex (6,24), gastrointestinal canal (12,18,21,23),myocardial and skeletal muscle (1,10,14),skin (3,11,26), and renal cortex (22). So far, only a few Received December 30,1991; accepted January 18,1993.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, LDF has proven useful for measurement of blood flow changes in the cerebral cortex (6,24), gastrointestinal canal (12,18,21,23),myocardial and skeletal muscle (1,10,14),skin (3,11,26), and renal cortex (22). So far, only a few Received December 30,1991; accepted January 18,1993.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler ultrasonography resulted in a high rate of false-negative and false-positive results in an experimental study by Dyess et al [14] . The superiority of laser Doppler flowmetry compared with ultrasound studies was shown [35] . Widely discussed limitations of this technique are that it is considered to be vulnerable to the signals from the neighboring large vessels, it requires an artery exposure and a pulsatile blood flow and a tissue contact is required which can impair local blood flow [1,29] .…”
Section: Doppler Ultrasoundmentioning
confidence: 99%
“…None of these methods, however, is commonly used clinically, because some are invasive and others are time consuming. Other methods to evaluate viability that are considered economical and clinically applicable include fluorescein assessment 6,7 , Doppler ultrasonography 8,9 and a laser Doppler technique 10,11 . However, fluorescein assessment lacks precision and sufficient objectivity, as it is based on a macroscopic impression of the intestinal microcirculation.…”
Section: Discussionmentioning
confidence: 99%